PENGELOLAAN KONFLIK KINERJA GURU (Studi Situs SMP Negeri 7 Klaten) - Fathoni, Ahmad; Muhibbin, Ahmad; Wariso, Wariso (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2013)
The aims of the research are to describe about: 1) Source and conflict types; 2) Conflict handling;and 3) Control conflict. Research type is qualitative. Research approach used is phenomenology. Researchsubject are headmaster and teachers. Data collecting methods are: in-depth interview, observation anddocumentation. Data analysis technique applies triangulation. The research result showed that 1) Source ofconflict, that is person or individual about differences in purpose, job (activity interdependence, difference ofvalues or perception about work load, and organizational about attainment of school programs; 2) Handling ofconflict is executed by constructing the side of related to conflicts, existence of communications to finalize activeproblem and role together, for example by the way of persuasion, drives a bargain, and self correction, and 3)Controlling conflict through competition, evasion, accommodation, compromise, and collaboration